Youth Sexuality: Behaviors, Attitudes and Differences by Sex and Personality Variables in Chilean University Students [Sexualidad Juvenil: Prácticas, Actitudes y Diferencias Según Sexo y Variables de Personalidad en Universitarios Chilenos] - Fernandez-Tapia, A; Celis-Atenas, K (2013)
Background: Sexual behavior usually begins in adolescence, and is mediated by biological, personality and socio-cultural variables which can affect the expression of preventive and risky sexual performance, as well as sex and age differences. Aim: To determine sex differences in the age of sexual initiation, the use of protective methods and mate selectivity in young men and women, as well as preventive practices according to age, and the prevalence of partner aggression. Subjects and Methods: Participants were 484 university students from public and private institutions, aged 22 ± 3 years (59% women) assessed using a diversity of self-report measures of personality traits, romantic relationship quality, sexual role, attachment type, socio-sexual openness, and self-esteem; they also answered questions regarding sexual behavior, and violence. Results: Differences in age of sexual initiation, risky sexual behavior, and socio-sexual openness were observed between men and women. Aggression prevalence in romantic relationships also varied according to sex and age. Similarities and differences in patterns of behavior and personality variables were observed in relationship quality, sexual role, kindness, and responsibility in males and females. Conclusions: The findings present consistencies with the international evidence and differences that may be due to context specificities, providing also an empirical referent to consider in health planning.